Monarchy, aristocracy, and the state in Europe 1300-1800 - Zmora, Hillay, 1964- (Historical connections., 2000)
This important new book takes a fascinating thematic approach, providing a useful survey of the position and role of the nobility in the government of states in early modern Europe.